2022
DOI: 10.1186/s12302-022-00684-2
|View full text |Cite
|
Sign up to set email alerts
|

The potential activity of biosynthesized silver nanoparticles of Pseudomonas aeruginosa as an antibacterial agent against multidrug-resistant isolates from intensive care unit and anticancer agent

Abstract: Background Antibiotic resistance is a global problem; especially the multidrug-resistant bacteria are a serious and fatal problem in the intensive care unit. Interestingly, biosynthesized silver nanoparticles are the promising key to eliminate these microbes. Using Pseudomonas aeruginosa supernatant is an easy and cheap method in silver nanoparticle biosynthesis. The biosynthesis conditions were adjusted, and the profiling of the biosynthesized silver nanoparticles was confirmed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The biosynthesized AgNPs showed a peak at 425 nm in UV/Visible spectral analysis. This result is in agreement with previous studies that confirmed the formation of AgNPs by other bacteria with the presence of the peak at 400–450 nm 35 . Analysis through an XRD spectrometer confirmed the presence of an elemental silver signal of the AgNPs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The biosynthesized AgNPs showed a peak at 425 nm in UV/Visible spectral analysis. This result is in agreement with previous studies that confirmed the formation of AgNPs by other bacteria with the presence of the peak at 400–450 nm 35 . Analysis through an XRD spectrometer confirmed the presence of an elemental silver signal of the AgNPs.…”
Section: Discussionsupporting
confidence: 94%
“…There has been no report of the use of bacteria closely related to P. canadensis for the synthesis of AgNPs. Although, other taxonomically related strains like P. hibiscicola , P. aeruginosa , and P. stutzeri have been reported for the synthesis of silver nanoparticles 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Already available on the market, silver nanoparticles (AgNPs) embedded into products offer a variety of benefits such as an antimicrobial functionalities by eradicating or inhibiting the growth of bacteria [1] , fungi [2] , and viruses [3] , as well as the ability to prolong the shelf life of products (i.e., food packaging). Their versatility renders them valuable in various products’ applications including wound dressings [4] , medical devices [5] , [6] , water purification systems [7] , and antibacterial coatings [8] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible strategy to manage resistance is to use combination treatment, especially with non-antibiotic drugs that may interact with antibiotics [55,56]. In this context, a prime non-antibiotic treatment is the use of silver nanoparticles (AgNPs) with powerful bactericidal properties against MDR microbes [57]. AgNPs facilitate antimicrobial uptake into bateria and lower the desired antibiotic dose required resulting in enhanced antimicrobial activity [58].…”
Section: Introductionmentioning
confidence: 99%